On the determinant of quaternionic polynomial matrices and its application to system stability - Pereira, Ricardo (2012)
In this paper, we propose a definition of determinant for quaternionic, polynomial matrices inspired by the well-known Dieudonne determinant for the constant case. This notion allows to characterize the stability of linear dynamical systems with quaternionic coefficients, yielding results which generalize the ones obtained for the real and complex cases.